The Effect of Workload and Job Stress on the Performance of Auditor Employees at PT Adis Dimension Footwear in Tangerang Regency - Adani, Alief Farhan; Soebadio, Bizzma Buana Amriki (AGUSPATI Research Institute, 2025)
The purpose of this study was to determine the influence of workload and job stress on the performance of Auditor employees at PT Adis Dimension Footwear, Tangerang Regency. This study used a quantitative descriptive method. The population in this study was all Auditor employees at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 40 respondents. This study used a saturated sampling technique because the population size was small, therefore the sample in this study used the entire population as respondents, namely 40 employees.The results of this study indicate that the coefficient of determination is indicated by R Square, which is 0.764, indicating that the magnitude of the influence of workload (X1) and job stress (X2) on employee performance variable (Y) is 76.4%. While the remaining 23.6% with SPSS 26 tools. (1) Partially, workload significantly affects the performance of Auditor employees at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by the calculated t value> t table (5.537>2.026) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work stress significantly affects the performance of Auditor employees at PT Adis Dimension Footwear, Tangerang Regency, which is indicated by the calculated t value> t table (3.712>2.026) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, workload and work stress significantly influence the performance of Auditor employees at PT Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (59.914>3.25) with a significance level of 0.000, thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that the workload and work stress variables, both partially and simultaneously, have a significant influence on the performance of Auditor employees at PT Adis Dimension Footwear, Tangerang Regency.